Syntrophic growth with direct interspecies electron transfer as the primary mechanism for energy exchange - Shrestha, Pravin Malla; Rotaru, Amelia-Elena; Aklujkar, Muktak; Liu, Fanghua; Shrestha, Minita; Summers, Zarath M.; Malvankar, Nikhil; Flores, Dan Carlo; Lovley, Derek R. (Environmental microbiology reports, 2013)
Summary Direct interspecies electron transfer (DIET) through biological electrical connections is an alternative to interspecies H2 transfer as a mechanism for electron exchange in syntrophic cultures. However, it has not previously been determined whether electrons received via DIET yield energy to support cell growth. In order to investigate this, co‐cultures of Geobacter metallireducens, which can transfer electrons to wild‐type G. sulfurreducens via DIET, were established with a citrate synthase‐deficient G. sulfurreducens strain that can receive electrons for respiration through DIET only. In a medium with ethanol as the electron donor and fumarate as the electron acceptor, co‐cultures with the citrate synthase‐deficient G. sulfurreducens strain metabolized ethanol as fast as co‐cultures with wild‐type, but the acetate that G. metallireducens generated from ethanol oxidation accumulated. The lack of acetate metabolism resulted in less fumarate reduction and lower cell abundance of G. sulfurreducens. RNAseq analysis of transcript abundance was consistent with a lack of acetate metabolism in G. sulfurreducens and revealed gene expression levels for the uptake hydrogenase, formate dehydrogenase, the pilus‐associated c‐type cytochrome OmcS and pili consistent with electron transfer via DIET. These results suggest that electrons transferred via DIET can serve as the sole energy source to support anaerobic respiration.